What do orange spots reveal about male (and female) guppies? A test using correlated responses to selection - Herdegen-Radwan, Magdalena; Cattelan, Silvia; Buda, Jakub; Raubic, Jarosław; Radwan, Jacek (Evolution, 2021)
Female preferences for male ornamental traits can arise from indirect benefits, such as increased attractiveness or better viability of progeny, but empirical evidence for such benefits is inconsistent. Artificial selection offers a powerful way to investigate indirect effects of male ornaments. Here, we selected for the area of orange spots on male guppies, a trait subject to female preferences in our population, in replicated up- and down-selected lines. We found a significant direct response to selection, and a correlated response in female preferences, with females from down-selected lines showing less interest in more orange males. Nevertheless, up-selected males sired more offspring in direct competition with low-selected males, irrespective of female origin. We did not find a significantly correlated response to selection among any other fitness correlates we measured. Our results imply that female preferences for orange spots can lead to increased reproductive success of their sons, with no effect on general viability of progeny. Furthermore, although we demonstrate that female preferences may evolve via linkage disequilibrium with the preferred trait, the potential for runaway selection by positive feedback may be constrained by the lack of corresponding linkage with male reproductive competitiveness.